2020
DOI: 10.2298/sarh200504028s
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on mental health services during the COVID-19 epidemic in Serbia

Abstract: World Health Organization (WHO) declared the COVID-19 outbreak a public health emergency of international concern. Mental health strategies implemented due to the coronavirus epidemic must include the assessment of mental health status of people in different subpopulations influenced by the COVID-19 outbreak, identifying persons who are at high risk of manifesting behavior disorders, suicide attempt, and aggression in aim of providing appropriate mental health care interventions for those in need. The target p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
10
0
3
Order By: Relevance
“…The first case of COVID-19 in Serbia was reported on 5 March 2020 and confirmed the day after [8]. The WHO declared the outbreak of global pandemic on 11 March 2020, and the Government of Serbia declared the state of emergency from 15 March 2020 until 6 May 2020 [9].…”
Section: Introductionmentioning
confidence: 94%
“…The first case of COVID-19 in Serbia was reported on 5 March 2020 and confirmed the day after [8]. The WHO declared the outbreak of global pandemic on 11 March 2020, and the Government of Serbia declared the state of emergency from 15 March 2020 until 6 May 2020 [9].…”
Section: Introductionmentioning
confidence: 94%
“…For example, the previous crises and times of uncertainty (e.g., SARS, H1N1 influenza) made us aware of long-term mental health issues (e.g., Liu et al, 2012 ; Sprang and Silman, 2013 ), which is aligned with more and more evidence stemming from the current pandemic (e.g., Wang et al, 2020 ; John et al, 2020 ). In Serbia, the existing data shows moderate to extreme levels of stress, depression, and anxiety among one third of the participants during the emergency state and the curfew ( Popov et al, 2021 ), as well as a significant proportion of those seeking mental health help due to anxiety ( Stašević-Karličić et al, 2020 ). Moreover, it was shown that a diagnosis of COVID-19 itself, and consequential physical distancing, was associated with feelings of isolation and loneliness ( Galea et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Serbia, a national psychological telephone support service during lockdown. One quarter of people who used this service was older than 70 years, 63.6% were women, and one third reported having symptoms of anxiety and feelings of tension during the COVID-19 epidemic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%